Change Management-Management Development - Cowan, M.Ed (Association for Talent Development, 1999)
Trainers must be comfortable with managing change to be effective organizational performance partners. Use this Infoline as a primer on change management tactics and the skills needed to facilitate change. This issue includes useful tools, hands-on examples, and models for change practitioners to use. In addition to a six-phase change strategy model, you will find a list of needed implementation skills, a performance issue analysis tool, and other important advice that will smooth the way of change and reduce barriers.